2018
DOI: 10.12669/pjms.346.15883
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Ramadan health seeking behavior, fasting trends, eating pattern and sleep cycle in pregnant women at a tertiary care institution of Pakistan

Abstract: Objective:To observe the pre-Ramadan health seeking behavior, fasting trends, eating pattern and, sleep cycle in pregnant women.Methods:It is a cross-sectional observational study, from July to September 2017, conducted at Tertiary Care Hospital in Karachi. The tool used for data collection was interviewer based closed ended questionnaire, 279 pregnant women who fasted during Ramadan were included in the study.Results:One to ten days of fasting was observed by 85.7% (198) of women. About 72.4% (202) never cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…To our knowledge, this is one of the first studies that examined the characteristics and outcomes of Ramadan fasting in pregnant women over a period of 10 years since most of the studies were conducted over one or few years. 5,8,[10][11][12][13][14][15] The rate of fasting in the current study (84.9%) was similar to the rate of a study conducted in Pakistan (82.8%) and another in Indonesia (80%). 5,13 Other studies showed a lower prevalence of fasting.…”
Section: Resultssupporting
confidence: 86%
“…To our knowledge, this is one of the first studies that examined the characteristics and outcomes of Ramadan fasting in pregnant women over a period of 10 years since most of the studies were conducted over one or few years. 5,8,[10][11][12][13][14][15] The rate of fasting in the current study (84.9%) was similar to the rate of a study conducted in Pakistan (82.8%) and another in Indonesia (80%). 5,13 Other studies showed a lower prevalence of fasting.…”
Section: Resultssupporting
confidence: 86%
“…111 The dietary habits with consumption of high carbohydrates, fats and sweets are common in Pakistan. 112 Lebanon, Jordan and Palestine In Lebanon, people with diabetes continue their daily work, but with less physical activity and less sleep. Usually, they consume two large meals between sunset and dawn.…”
Section: Pakistanmentioning
confidence: 99%
“…Masood et al [42] observed the pre-Ramadan health-seeking behavior, fasting trends, eating pattern, and sleep cycle in pregnant women in a cross-sectional observational study in Karachi. The tool used for data collection was interviewer-based closed-ended questionnaire.…”
Section: Antenatal Care During Ramadanmentioning
confidence: 99%